2019
DOI: 10.1007/978-3-030-26203-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Gender Differences in Computer and Information Literacy

Abstract: As computer and information technologies increasingly dominate modern life, educators and policymakers recognize the importance of ensuring that all students are able to use computers to investigate, create, and communicate effectively. Intriguingly, results from IEA's International Computer and Information Literacy Study (ICILS) of grade eight students, undertaken in 2013, indicated that female students generally had higher computer and information literacy (CIL) scale scores than male students. This book fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
11
1
1
Order By: Relevance
“…In addition, a recently published meta-analysis on gender and attitudes towards ICT found a small but significant positive effect, suggesting that male participants hold more favourable attitudes (Cai et al 2016). In contrast, a study by Gebhardt et al (2019) found gender differences only in country-level analyses. Thus, it would be meaningful to explore whether this holds true for the German pre-service teacher sample in comparison to other countries.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, a recently published meta-analysis on gender and attitudes towards ICT found a small but significant positive effect, suggesting that male participants hold more favourable attitudes (Cai et al 2016). In contrast, a study by Gebhardt et al (2019) found gender differences only in country-level analyses. Thus, it would be meaningful to explore whether this holds true for the German pre-service teacher sample in comparison to other countries.…”
Section: Discussionmentioning
confidence: 95%
“…However, the topic of gender differences appears to be complex, as empirical research has yielded mixed evidence on the impact of gender on ICT-related constructs (Hatlevik and Arnseth 2012;Siddiq et al 2015). With respect to ICT self-efficacy, the ICILS reported that male teachers showed higher ICT self-efficacy than female teachers (Gebhardt et al 2019). Additionally, a higher percentage of female than male teachers reported using ICT in their instruction.…”
Section: Gender Differences and Ictmentioning
confidence: 99%
“…In turn, other studies found that female students had on average a higher skill level than boys (ACARA 2015; Aesaert and van Braak 2015;Fraillon et al 2014Fraillon et al , 2019Gebhardt et al 2019;Thomson 2015). In Australia, for instance, it was observed that girls in sixth and tenth grade classes displayed a higher computer and information literacy than boys (ACARA 2015(ACARA , 2018.…”
Section: Fig 1 Icils 2013 Framework Modelmentioning
confidence: 91%
“…Sex and gender differences in digital literacy [12], use [13,14] and preferences [15] of mHealth apps, as well as online health information seeking [16,17] have been previously reported. Overall, women tend to report more eHealth and mHealth usage compared to men, but this seemed to be limited to high-income countries [18].…”
Section: Introductionmentioning
confidence: 86%